Crystal structure of bis(μ-benzeneselenolato)-(μ-[N-benzyl-N-(diphenylphosphanyl)-P,P-diphenylphosphinous amide])-tetracarbonyl diiron (Fe–Fe), C47H37Fe2NO4P2Se2 - Bai Shu-Fen; Lü Shuang; Li Qian-Li (Zeitschrift für Kristallographie - New Crystal Structures)
C47H37Fe2NO4P2Se2, monoclinic, P21/n (no. 14), a = 12.8144(11) Å, b = 17.9714(15) Å, c = 19.1077(17) Å, β = 104.329(4)°, V = 4263.5(6) Å3, Z = 4, R gt(F) = 0.0420, wR ref(F 2) = 0.0968, T = 298(2) K.